2008
DOI: 10.1016/j.chembiol.2008.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Insights of the Early Glycosylation Steps in Calicheamicin Biosynthesis

Abstract: Summary The enediyne antibiotic calicheamicin (CLM) γ1I is a prominent antitumor agent that is targeted to DNA by a novel aryltetrasaccharide comprised of an aromatic unit and four unusual carbohydrates. Herein we report the heterologous expression and the biochemical characterization of the two ‘internal’ glycosyltransferases CalG3 and CalG2 and the first structural elucidation of an enediyne glycosyltransferase (CalG3). In conjunction with the previous characterization of the ‘external’ CLM GTs CalG1 and Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 70 publications
1
55
0
Order By: Relevance
“…CLM α 3 I was provided by Pfizer. CLM T 0 was prepared as previously described (16). CalG3, CalG2, and CalG1 with TDP samples were prepared by mixing 10 mg∕mL of CalG3 or 20 mg∕mL of CalG2 or CalG1 protein samples with 25 mM TDP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CLM α 3 I was provided by Pfizer. CLM T 0 was prepared as previously described (16). CalG3, CalG2, and CalG1 with TDP samples were prepared by mixing 10 mg∕mL of CalG3 or 20 mg∕mL of CalG2 or CalG1 protein samples with 25 mM TDP.…”
Section: Methodsmentioning
confidence: 99%
“…1). Some CLM GTs are highly promiscuous and can perform forward, reverse, and exchange reactions, enabling chemoenzymatic methods to generate glycodiversified CLM analogs (15,16). Based upon biochemical studies, CalG1 and CalG4 were found to be external GTs, acting as a rhamnosyltransferase for sugar moiety D and as an aminopentosyltransferase for sugar moiety E, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cpz31, together with most glycosyltransferases involved in natural product biosynthesis, belongs to the GT-1 family of glycosyltransferases as classified by the CAZy system (6). Cpz31 exhibits significantly higher homology to, for example, the 4,6-dideoxy-4-hydroxylamino-␣-Dglucosyltransferase CalG3 (36% identity, 50% similarity) from Micromonospora echinospora (59) than to the rhamnosyltransferases AraGT (29% identiy, 38% similarity) from S. echinatus (38) and SpnG (29% identity, 39% similarity) from Saccharopolyspora spinosa (5). Luzhetskyy et al (39) proposed that similarity-based relationships of glycosyltransferases are better understood with consideration of the aglycone substrate than of the sugar donor.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, increasing evidence has demonstrated a certain degree of flexibility in GTFs regarding the acceptor substrate (7,12,26,27) and, most frequently, the donor substrate (2,5,17,22). X-ray structures of some GTFs involved in antibiotic biosynthesis have been reported: GtfA, GtfB, and GtfD in glycopeptide biosynthesis (14)(15)(16); AviGT4 in avilamycin A biosynthesis (11); UrdGT2 in urdamycin A biosynthesis (13); and CalG34 in calicheamicin biosynthesis (28). In addition, the structures of two other GTFs involved in antibiotic biosynthesis and resistance have been reported (3).…”
mentioning
confidence: 99%